A dimensão jurídica do direito à cidade: conteúdo, estrutura normativa e operacionalidade - Carvalho, Harley Sousa de (2023)
The following doctoral research is theoretical and qualitative in nature. It is, first and foremost, based on bibliographical research and, as a complement, on jurisprudential and documental research. The initial question of this research, from which other specific questions unfold, is: would it be possible to develop an approach to the right to the city which is solely based on a specifically legal theorization? The work demonstrates and defends the existence of multiple readings of the right to the city and the unfinished task of a legal theorization, especially on how it should influence legal interpretation and application. These issues are brought to the fore in chapters 2 (philosophical issues) and 3 (political issues). To overcome the lack of a legal theory on the right to the city, a legal-dogmatic (chapter 4) and theoretical-reflexive analysis is carried out which goes through the issues of content, normative structure and conceptual operationality. Based on Marcelo Neves' principiological theory, it is argued that the right to the city can help in the adequate heteroreference of the legal system, to produce a cognitive opening that does not eliminate the operational autonomy of the legal system. Despite the economic, social, legal and political challenges to the realization of the right to the city (chapter 5), which have intensified in the last decade, it is proposed that a legal approach should guide the interpretation and application of legal-urban norms in order to guarantee the coherence and systemic cohesion of urban law, curbing spaces of urban exception which, in turn, disintegrate the public interest. The importance of enabling the spatialization and materialization of fundamental rights is also proposed, breaking the formal and deterritorialized approach to fundamental rights. Furthermore, the duty of judicial and administrative decisions to operate with a view to maximizing and strengthening the right to the city is pointed out, breaking away from a merely symbolic use (chapter 6).